Trans-dominant inhibitory human immunodeficiency virus type 1 protease monomers prevent protease activation and virion maturation. - Babé, L M (1995)
Production of infectious human immunodeficiency virus (HIV) requires proper polyprotein processing by the dimeric viral protease. The trans-dominant inhibitory activity of a defective protease monomer with the active site Asp-25 changed to Asn was measured by transient transfection. A proviral plasmid that included the drug-selectable Escherichia coli gpt gene was used to deliver the wild-type (wt) or mutant proteases to cultured cells. Coexpression of the wt proviral DNA (HIV-gpt) with increasing amounts of the mutant proviral DNA (HIV-gpt D25N) results in a concomitant decrease in proteolytic activity monitored by in vivo viral polyprotein processing. The viral particles resulting from inactivation of the protease were mostly immature, consisting predominantly of unprocessed p55gag and p160gag-pol polyproteins. In the presence of HIV-1 gp160 env, the number of secreted noninfectious particles correlated with the presence of increasing amounts of the defective protease. Greater than 97% reduction in infectivity was observed at a 1:6 ratio of wt to defective protease DNA. This provides an estimate of the level of inhibition required for effectively preventing virion processing. Stable expression of the defective protease in monkey cells reduced the yield of infectious particles from these cells by 90% upon transfection with the wt proviral DNA. These results show that defective subunits of the viral protease exert a trans-dominant inhibitory effect resulting from the formation of catalytically compromised heterodimers in vivo, ultimately yielding noninfectious viral particles.